2011
DOI: 10.1038/aps.2011.91
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of novel anti-HIV agent 3-cyanomethyl-4-methyl-DCK by human liver microsomes and recombinant CYP enzymes

Abstract: Aim:To investigate the metabolism of 3-cyanomethyl-4-methyl-DCK (CMDCK), a novel anti-HIV agent, by human liver microsomes (HLMs) and recombinant cytochrome P450 enzymes (CYPs). Methods: CMDCK was incubated with HLMs or a panel of recombinant cytochrome P450 enzymes including CYP1A2, 2B6, 2C8, 2C9, 2C19, 2D6, 3A4, and 3A5. LC-ion trap mass spectrometry was used to separate and identify CMDCK metabolites. In the experiments with recombinant cytochrome P450 enzymes, specific chemical inhibitors combined with CYP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The amount of parent drug was analyzed by LC-MS/MS and the percent of remaining parent drug was calculated and compared. In vitro permeabilities of PQ-69 and DPCPX were carried out using a Caco-2 cell line, according to previously described methods [16]. In brief, drug solution (5 μM) was placed in the donor chamber and samples were taken from the receptor chamber at 90 min.…”
Section: Measurement Of Pa2 Valuesmentioning
confidence: 99%
“…The amount of parent drug was analyzed by LC-MS/MS and the percent of remaining parent drug was calculated and compared. In vitro permeabilities of PQ-69 and DPCPX were carried out using a Caco-2 cell line, according to previously described methods [16]. In brief, drug solution (5 μM) was placed in the donor chamber and samples were taken from the receptor chamber at 90 min.…”
Section: Measurement Of Pa2 Valuesmentioning
confidence: 99%
“…Consequently, it is not surprising to note that KDs feature low metabolic stability and low bioavailablity in most cases. Not only the enzymes in liver and gut, but also the carboxylesterases in rat plasma were reported to possess the catalytic abilities for KDs [7,9,10,40,50,54,56,57,58]; however, the gut bacteria-catalyzed metabolism hasn′t been reported for this kind of coumarins [54]. Taking l PA ( 3 ) for instance, its prototype is undetectable even following intravenous administration, let alone oral treatment, while most portion of d PA ( 2 ) can be quickly metabolized into l CK ( 14 ) and some other metabolites owing to the extensive distribution of isozymes in both intestine and liver tissues.…”
Section: Metabolism Of Khellactone Derivativesmentioning
confidence: 99%
“…Tandem mass spectrometric platforms, including ion trap, hybrid triple quadrupole-linear ion trap and time-of-flight mass spectrometry have been demonstrated as the reliable tools to plausibly identify the metabolites in vitro and in vivo . The fragmentation patterns of KDs have been previously proposed by various mass spectroscopic techniques [6,58]: initially, neutral loss takes place at the C-4′ position to afford a stable intermediate residue; the intermediate ion will subsequently cleave another neutral molecule from the C-3′ position to produce a diagnostic fragment ion at m / z 227 or remove an acyl group to yield the other characteristic signal at m / z 245. The cracking rules proposed for KDs are illustrated in Figure 2.…”
Section: Metabolism Of Khellactone Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro study indicated that CMDCK was a CYP3A4 substrate and could be metabolically eliminated rapidly in liver and intestinal microsomes. Known CYP3A4 inhibitors, such as ritonavir and ketoconazole, had significant inhibitory effects on its liver and intestinal metabolism [14]. Low solubility and extensive metabolism of CMDCK limited its oral bioavailability.…”
Section: Pharmacokinetic Studymentioning
confidence: 99%